Design usability study and new tv remote control unite - Zhang, Lu (2014)
Television remote control may have been the biggest innovation of convenience since it was invented. With the florescence of technologies presented, traditional remote control would not be able to satisfy new user experiences and their future expectations. Hence, the absolute need of future interactions between the TV and users are presented. By studying the related literature as well as conducting a market research in both the existing products and future technology trends helped the author to generate a better understanding of current market. In order to understand customers’ needs in a deeper level, several surveys were conducted to gather voice of customers as many as possible. By analyzing the results gathered, essential customer feedbacks, user experiences as well as their expectations were collected which was a key contribution to the concept generation stage later. Several concepts were generated through the use of functional analysis followed by the morphological chart, which was draw through transforming the insight gain from the survey results and brainstorming new ideas, this was done to identify the important components needed in the design concepts. By analyzing the concepts generated, massive discussions and evaluations were done to make sure the final concept was right in the track with customer’s voice as well as the future concept. Several Mock-ups were made and tested by undergoing focus group surveys for their usability. Hence, another run of evaluations and modifications were done based on the results generated and a final version of the design was therefore purposed.